Cosplay : the fictional mode of existence - Lunning, Frenchy (University of Minnesota Press, 2022)
An exploration of cosplay and its relationship with the realms of its global fandom, performance, and the modes of fictional existence Flourishing far beyond its Japanese roots, cosplay has become an international phenomenon with fervid fans who gather at enormous, worldwide conventions annually. Here, author Frenchy Lunning offers an intimate, sensational tour through cosplay's past and present, as well as its global lure. Through a culmination of years of personal research on cosplay, and growing out of Lunning's wealth of scholarship, conference presentations, and cosplayer interviews, Cosplay is a unique and necessary examination of identity, performance, play, and otaku fandom and culture in relation to contemporary theories. With discussions covering construction, masquerades, and community through performance, Lunning presents cosplay as a dynamic and ever-evolving global practice. She combines the fascinating viewpoints of cosplayers with observational, in-depth research on cosplay history and practice, and a deep dive into critical theory involving the modes of fictional existence, in order to understand its global expansion. Augmented with beautiful photographs, this is an engrossing, lively read that explores a complicated and often misunderstood history and meditates on how cosplay allows its participants to create and construct meaning and identity.
Keywords: Cosplay.; Costume.; Costume design.; Role playing.; Performance art.; Role Playing; Costumade.; Costume (Arts décoratifs) -- Création.; Jeu de rôle.; Manœuvre artistique.; costume design.; Cultural.; Anthropology.; SOCIAL SCIENCE.; Media Studies.; Cosplay; Costume; Costume design; Performance art; Role playing